2021
DOI: 10.3390/ijerph18168304
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Antibiotic Resistance Co-Selection in Bacillus sp. Isolates from the Almadén Mining District

Abstract: Antibiotic resistance (AR) in the environment is of great global concern and a threat to public health. Soil bacteria, including Bacillus spp., could act as recipients and reservoirs of AR genes of clinical, livestock, or agricultural origin. These genes can be shared between bacteria, some of which could be potentially human pathogens. This process can be favored in conditions of abiotic stress, such as heavy metal contamination. The Almadén mining district (Ciudad Real, Spain) is one of the environments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…Soils, especially those under high environmental pressure, act as a natural reservoir of resistance to existing antibiotics or provide the potential to host bacteria of clinical importance ( Yan et al, 2020 ; Liao et al, 2021 ). Several studies show the existence of a co-choice between the presence of various toxic compounds in the environment and the selection of antibiotic resistance naturally, together with co-resistance to heavy metals and antibiotics ( Yan et al, 2020 ; Mazhar et al, 2021 ; Robas et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Soils, especially those under high environmental pressure, act as a natural reservoir of resistance to existing antibiotics or provide the potential to host bacteria of clinical importance ( Yan et al, 2020 ; Liao et al, 2021 ). Several studies show the existence of a co-choice between the presence of various toxic compounds in the environment and the selection of antibiotic resistance naturally, together with co-resistance to heavy metals and antibiotics ( Yan et al, 2020 ; Mazhar et al, 2021 ; Robas et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The mer operon encodes a common mercury resistance mechanism that is often carried by transposons and a wide range of plasmids that are ubiquitous in Proteobacteria [ 64 , 65 , 66 ]. Previous studies have reported significant co-occurrence of mer operon and AMR genes in mobile elements in a range of isolates, demonstrating that mercury facilitates the selection of multidrug-resistant strains [ 67 , 68 , 69 ]. Thus, the acquisition of mercury resistance genes by Alcaligenes isolates is likely adaptive in clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…Lately, the environmental co-selection of resistance to cephalosporins and tetracyclines by selective mercury pressure has been demonstrated in Bacillus spp. isolates from a mining district in Almadén, Spain ( Robas et al, 2021 ). Thus, our results reinforced the evidence about the correlation between antibiotic resistance and mine-related contamination.…”
Section: Resultsmentioning
confidence: 99%